2020
DOI: 10.1016/j.compscitech.2020.108154
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxially stretched polyethylene/boron nitride nanocomposite films with metal-like thermal conductivity

Abstract: Achieving ultra-high thermal conductivity while maintaining the electrical insulation of polymers is highly desirable for many applications such as thermal management and packaging. In this work, polyethylene / boron nitride nanoplatelets (PE/BNNP) nanocomposite film was produced through melt processing followed by uniaxial stretching. Microstructural analysis reveals that the stretched composite film features a co-continuous network structure which consists of oriented lamellae bridged by both stretched polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…In the first section, we mentioned the overall thermal conductivity of composites can be improved by the ultra-high thermal conductivity of BNs, such as building a 3D network [ 88 , 89 , 90 , 91 , 92 , 93 ]. Hou et al [ 94 ] employed this principle to make BNs fibers.…”
Section: Modification Of Thermal Characteristics Of Epoxy Resin Composite Foam Insulation Materialsmentioning
confidence: 99%
“…In the first section, we mentioned the overall thermal conductivity of composites can be improved by the ultra-high thermal conductivity of BNs, such as building a 3D network [ 88 , 89 , 90 , 91 , 92 , 93 ]. Hou et al [ 94 ] employed this principle to make BNs fibers.…”
Section: Modification Of Thermal Characteristics Of Epoxy Resin Composite Foam Insulation Materialsmentioning
confidence: 99%
“…Test specimens were cut into 75 mm squares and were clamped using 24 nitrogen-driven pneumatic clamps of the biaxial stretching machine. More detailed configuration of the biaxial stretching machine can be found in (Martin et al, 2005;Zhang et al, 2020). It was found that only unfilled PP and PP/5wt % GNP can be successfully biaxially stretched to SR2.…”
Section: Biaxial Stretching Of Pp/gnp Compositesmentioning
confidence: 99%
“…However, the low thermal conductivity of bulk polymer in range of 0.1-0.5 W m −1 K −1 limits extensive applications which need high heat conduction. [3] It is undeniable that polymers could show higher thermal conductivity with higher crystallite orientation and crystallinity, higher chain alignment, lower entangling, and stronger interchain interactions. [4] Recently, research from Xu et al showed thermal conductivity of polyethylene (PE) films as high as 62 W m −1 K −1 by minimally entangling and maximally aligning the chain.…”
Section: Introductionmentioning
confidence: 99%